Quality of life improvement model for flood victims at temporary flood transfer center / Nik Fakrulhazri Nik Hassan ... [et al.] - Nik Hassan, Nik Fakrulhazri; Che Hamid, Azemi; Abdul Rahman, Baharom; Ahmad, Zuriyati; Mohamad, Zuraida; Baharuddin, Nurul Syuhada (2018)
The analysis from previous studies found that the low of quality of life (QoL) in the Temporary Transfer Center (TFTC) cause of lack of facilities provided and facing with a lot of management issues including exposing to dangerous diseases cause by water pollution during flood event. Normally, number of studies show that research regarding to QoL more focusing on four major domains, namely physical health, mental health, social support and environment. In order to improve flood victims living condition at TFTC, this research attention to proposing spirituality into QoL model. By using IBM SPSS AMOS, the results indicates that proposing QoL Model among Flood Victims at TFTC consist with physical health, mental health, social support, and environment and together with spirituality was proven in good fit. This study was using Confirmatory Factor Analysis (CFA), CFI, TLI, and RMSEA values in order to confirm the model in good fit. According to CFA, only 4 items spirituality elements remain and focusing on inner spirituality such as believing on fate, flood disaster as a test in their life, and believe there wisdom behind what happens. The next attention of this study to observing in difference way perspective by identify the potential an element under sub domains based on life of humanity toward level of QoL among flood victims. Therefore, this study also aims to identify the needs and services required by the flood victims at TFTCs. By using IBM SPSS Statistics and AMOS, the results indicate that Flood Victims Quality of Life Index (FVQoL-lndex’17) was positively in order to predict the level of QoL among flood victims at TFTC. The findings from this study reveal that FVQoL-lndex’17 allowed to measure meaningful differences between states in the East Coast of Malaysia and each sub-indexes especially in being and becoming domains. The findings also found that the shortage faced by the flood victims was in line with the needs and services required at TFTC. The data was conducted during flood events occur at East Coast Region of Malaysia from November 2016 until May 2017.